Obesity in children: bariatric surgery - Canoy, D; Yang, T (BMJ Publishing Group, 2015)
INTRODUCTION: The prevalence of childhood obesity in the UK and in many countries worldwide remains high. Behavioural interventions to modify lifestyle, such as diet and physical activity, usually form part of weight management strategies for obese children. Whether or not surgical interventions are effective and safe in treating childhood obesity is unclear. METHODS AND OUTCOMES: We conducted a systematic overview, aiming to answer the following clinical question:What are the effects of surgical interventions for the treatment of childhood obesity? We searched Medline, Embase, The Cochrane Library, and other important databases up to August 2014 (BMJ Clinical Evidence reviews are updated periodically; please check our website for the most up-to-date version of this overview). RESULTS: At this update, after deduplication and removal of conference abstracts, 67 records were screened for inclusion in the overview. Appraisal of titles and abstracts led to the exclusion of 19 studies and the further review of 48 full publications. Of the 48 full articles evaluated, two systematic reviews were included at this update. CONCLUSIONS: In this systematic overview, we categorised the efficacy for two comparisons based on information about the effectiveness and safety of bariatric surgery versus no intervention and different types of bariatric surgery versus each other.